Micro-segmented flow : Applications in chemistry and biology - Cahill, Brian P.; Kohler, J. Michael (Biological and Medical Physics, Biomedical Engineering, 2014)
The book is dedicated to the method and application potential of micro segmented flow. The recent state of development of this powerful technique is presented in 12 chapters by leading researchers from different countries. In the first section, the principles of generation and manipulation of micro-fluidic segments are explained. In the second section, the micro continuous-flow synthesis of different types of nanomaterials is shown as a typical example for the use of advantages of the technique in chemistry. In the third part, the particular importance of the technique in biotechnical applications is presented demonstrating the progress for miniaturized cell-free processes, for molecular biology and DNA-based diagnostis and sequencing as well as for the development of antibiotics and the evaluation of toxic effects in medicine and environment.